(3TQM MOjK Pi GdjOjf (B[ (3GdcdGe Ydi SLhO GdSgh (B]s - (3Ndjd Hf cjcdOj Hf YHO Gddg GdYdGFj GdOeTbqj, CHh SYjO, UdGM GdOjf , J (B761 (3g`s
(3ChdgG (B:s
(3bGd QMeg Gddg CHhGH SLhO GdSgh HGH eG LGA ajef Sde ef fbUGf s
(3BNQgG (B:s
(3hbO bGd GdfHi Udi Gddg Ydjg hSde (B: (3EfeG GdCYeGd HGdfjI hEfeG dGeQF eG fhi hGddg SHMGfg CYde BNQ TQM MOjK Pi GdjOjf QVi Gddg Yfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs